Konsep Persaudaraan Intra Agama Islam dalam Tafsir Nadhmuddurar Karya Al-Biqa'i - Abdul Hannan Ar-Rifa'i (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
This study aims to explain and explain the concept of brotherhood in Islamaccording to al-Biqa'i in the Nadhmuddurar commentary book. This research waswritten using a literature study (Library Research) by reading and reviewing theliterature that became the object of the research study. Based on this research, it canbe concluded that al-Biqa'i in his book Nadhmuddurar explains the meaning ofbrotherhood and unity that cannot be separated because these two things are veryurgent for the future of Muslims. Even in detail he explained that the degree orposition of humans is not seen from lineage or descent but from piety.